PENERAPAN METODE CIRC DALAM MENINGKATKAN MAHARAH QIRA’AH SISWA PADA PEMBELAJARAN BAHASA ARAB - Nur, Robiyah; Aziz Zawawi, Fahmi; Basyar, Syaripuddin; Fauziah, Asti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the effectiveness of the Cooperative Integrated Reading and Composition (CIRC) method in improving the maharah qira’ah (reading skills) of fifth-grade students at SD Islam Assalam Bandar Lampung. A quasi-experimental design was employed, with two groups: an experimental class using the CIRC method and a control class using conventional teaching methods. Data were collected through pre-test and post-test assessments. The results indicate that the CIRC method significantly enhances students' reading comprehension, as evidenced by a higher N-Gain score in the experimental class compared to the control class. The CIRC method encourages active student participation through group discussions, summarization, and peer-assisted learning, leading to improved reading comprehension and engagement. The study also highlights the potential of cooperative learning strategies in Arabic language education, particularly in fostering critical thinking and collaborative problem-solving. Despite its effectiveness, some challenges were identified, such as ensuring equal participation among students and managing class time efficiently. This study contributes to the adaptation of the CIRC method in Arabic language learning at the elementary level, an area that has received limited research attention. It recommends that teachers integrate CIRC as an alternative instructional strategy to enhance students' Arabic reading skills. Future research should explore the integration of digital learning tools with CIRC to further optimize its effectiveness in the modern educational context.